Telomeric TART elements target the piRNA machinery in Drosophila - Ellison, Christopher E. (PLoS Biol, 2020)
Coevolution between transposable elements (TEs) and their hosts can be antagonistic, where TEs evolve to avoid silencing and the host responds by reestablishing TE suppression, or mutualistic, where TEs are co-opted to benefit their host. The TART-A TE functions as an important component of Drosophila telomeres but has also reportedly inserted into the Drosophila melanogaster nuclear export factor gene nxf2. We find that, rather than inserting into nxf2, TART-A has actually captured a portion of nxf2 sequence. We show that TART-A produces abundant Piwi-interacting small RNAs (piRNAs), some of which are antisense to the nxf2 transcript, and that the TART-like region of nxf2 is evolving rapidly. Furthermore, in D. melanogaster, TART-A is present at higher copy numbers, and nxf2 shows reduced expression, compared to the closely related species Drosophila simulans. We propose that capturing nxf2 sequence allowed TART-A to target the nxf2 gene for piRNA-mediated repression and that these 2 elements are engaged in antagonistic coevolution despite the fact that TART-A is serving a critical role for its host genome.